Pengabdian Masyarakat Melalui Seminar Parenting di SPS Patriotik, Desa Bube Baru, Kecamatan Suwawa, Kabupaten Bone Bolango, Provinsi Gorontalo - Felista Mohamad; Nurfadilah Muthalib; Rapi US. Djuko; Fiola Indah Putri Pratama; Nunung Suryana Jamin; Try Hastri Bumulo; Nurul Aini Sodik (Pusat Riset dan Inovasi Nasional, 2026)
This parenting seminar was designed to increase parents' capacity to understand and implement integrative holistic parenting, encompassing education, health, nutrition, and psychosocial aspects of children. An integrative holistic approach is considered important because child growth and development are influenced not only by formal education but also by health conditions, adequate nutrition, and emotional and social support from the family environment. This activity aims to provide comprehensive education to parents so they can carry out their parenting role optimally and sustainably. The activity was implemented using an interactive seminar method involving the delivery of material by competent speakers in the fields of childcare, education, and health, accompanied by discussions and a question-and-answer session that encouraged active participant participation. The material presented focused on understanding the concept of integrative holistic parenting, strategies for implementing positive parenting patterns, and the role of parents in supporting children's physical, emotional, social, and cognitive development. The results of the activity showed a significant increase in parents' knowledge, understanding, and attitudes regarding the importance of comprehensive and integrated parenting. Parents became more aware of their role as key figures in shaping character and optimizing children's potential from an early age. This seminar made a real contribution in equipping parents to be able to create a healthy, safe, and supportive parenting environment. This activity is expected to become a model for developing parental capacity in a sustainable manner with an integrative holistic approach as the key to successful child growth and development.